Benefit of Early versus Deferred Antiretroviral Therapy on Progression of Liver Fibrosis among People with HIV in the START Randomized Trial. Issue 3 (19th February 2019) - Dharan, Nila J.; Neuhaus, Jacqueline; Rockstroh, Juergen K.; Peters, Lars; Gordin, Fred; Arenas‐Pinto, Alejandro; Emerson, Carol; Marks, Kristen; Hidalgo, Jose; Sarmento‐Castro, Rui; Stephan, Christoph; Kumarasamy, Nagalingeswaran; et al.
Abstract : The role of antiretroviral therapy (ART) in reducing or contributing to liver fibrosis in persons with human immunodeficiency virus (HIV) is unclear. We evaluated participants in the Strategic Timing of AntiRetroviral Treatment (START) trial for liver fibrosis using the AST to Platelet Ratio Index (APRI) and Fibrosis‐4 Index (FIB‐4), and assessed for a benefit of early versus delayed ART on liver fibrosis progression. ART‐naïve persons with high CD4 counts (>500 cells/µL) from 222 clinical sites in 35 countries were randomized to receive ART either at study enrollment (immediate treatment arm) or when their CD4 count fell below 350 cells/µL (deferred treatment arm). The following outcomes were evaluated: fibrosis (APRI > 0.5 or FIB‐4 > 1.45), significant fibrosis (APRI > 1.5 or FIB‐4 > 3.25), hepatic flare, and resolution of elevated APRI and FIB‐4 scores. Of the 4, 684 enrolled into the START study, 104 did not have APRI or FIB‐4 results and were excluded. Among 4, 580 participants (2, 273 immediate treatment; 2, 307 deferred treatment), the median age was 36 years, 26.9% were female, and 30.4% were black. Three percent had an alcoholism or substance abuse history, 6.4% had hepatitis B and/or C, and 1.1% had significant fibrosis at baseline. The median CD4 count was 651, and 5.3% had HIV RNA ≤ 200. Immediate arm participants were at lower risk of developing increased fibrosis scores than deferred arm participants (hazard ratio [HR] = 0.66; 95% confidence interval [CI] = 0.57‐0.78; P < 0.001) and more likely to have resolution of elevated baseline scores (HR 1.6; 95% CI 1.3‐1.9; P < 0.001). Conclusions: Significant liver fibrosis was rare among ART‐naïve HIV‐positive persons with high CD4 counts. Our findings suggest a benefit of early ART in preventing the development of liver fibrosis.